Asimetri Syarat Domisili Instrumen Bukti Waris dalam Pendaftaran Tanah: Telaah Yuridis-Maslahat - Dita Ananda Kasih (Lembaga Yasin AlSys, 2026)
Although the domicile clause in Article 111 paragraph (1) letter c number 5 of the Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency Number 16 of 2021 has been widely discussed, previous studies have tended to understand it as a stand-alone vertical conflict between the ministerial regulation and the Notary Office Law, thereby failing to reveal the asymmetry among the six instruments of inheritance evidence regulated in the same article. This study aimed to analyze this internal asymmetry and examine it based on the principles governing the substance of legislation and the doctrine of maslahah. This study employed a prescriptively oriented normative juridical method using statutory, conceptual, and case approaches. The units of analysis comprised six instruments of inheritance evidence, four regulatory instruments, and Supreme Court Decision Number 29/P/HUM/2022, which were purposively selected. Legal materials were collected through document study and analyzed using a normative comparison matrix and systematic, grammatical, and teleological interpretations. The results showed that only two of the six instruments of inheritance evidence contained territorial restrictions with different characteristics, namely a restriction inherent in the office in the first instrument and a restriction imposed externally in the second instrument. Notaries, as functional public officials with a territorial jurisdiction covering one province, are restricted to the regency or city of the decedent’s domicile, whereas Balai Harta Peninggalan, which has only five offices with jurisdictions spanning multiple provinces, is not subject to a similar restriction. This asymmetry burdens heirs without producing commensurate benefits and fails to satisfy the principle of effectiveness and the criterion of maslahah. This study introduces the concept of intra-article normative asymmetry as an analytical framework for assessing regulatory imbalances within a single article and recommends reformulating the domicile clause based on the notary’s territorial jurisdiction to establish more consistent, effective, and equitable regulation of inheritance evidence.